The Concept of “Regulation by Insurance” from an Indonesian Legal Perspective: A Study on the Effectiveness of Insurance as a Modern Risk Management Tool - Ajeng Ayu Elysia Fernanda; Abida Raiha Agniarga; Rida Dwi Marganingrum; Atikah Nur Ainani Putri; Tiara Saresty Dinda Pregiwati (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This article examines the evolving concept of “regulation by insurance” within the Indonesian legal system, addressing the central problem of whether insurance can function effectively as a modern regulatory instrument beyond its traditional role as a contractual risk transfer mechanism. The study identifies a doctrinal gap in Indonesian law, particularly under Law No. 40 of 2014 on Insurance, which has not explicitly recognized the regulatory capacity of insurance despite its practical influence on behavior through underwriting standards, premium differentiation, and contractual obligations. This research employs a normative legal methodology, incorporating doctrinal and comparative approaches through the analysis of statutory regulations, legal principles, scholarly doctrines, and comparative legal frameworks to construct a comprehensive understanding of insurance as a governance tool. The findings reveal that insurance in Indonesia possesses latent regulatory characteristics that align with global developments, yet remains fragmented and insufficiently articulated within the legal framework. The discussion demonstrates that technological advancements such as insurtech and blockchain, alongside risk management theory and ethical models such as takaful, further reinforce the regulatory potential of insurance while simultaneously exposing normative and institutional limitations. The study concludes that a doctrinal reconstruction is necessary to formally integrate insurance as a hybrid regulatory regime within Indonesian law, thereby enhancing its effectiveness in addressing complex and modern risk environments.